DIGITAL HUMAN MODELING FOR ERGONOMIC ASSESSMENT OF SEATED CNC OPERATOR - Kshirsagar, V. P.; Awari, G. K.; Singh, M. P. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Digital Human Modeling (DHM) is a widely used tool for ergonomic assessments in industrial workplaces, particularly in Computer Numerical Control (CNC) operations were seated operators face work-related musculoskeletal disorders (WMSDs) due to prolonged postures and repetitive tasks. This study evaluates ergonomic risks among seated CNC operators using DHM tools. The methodology involves posture analysis, anthropometric data integration, and ergonomic assessment techniques such as Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA). The findings provide insights into workstation design improvements and ergonomic interventions, ensuring safer and more comfortable working conditions. Digital Human Modeling plays a pivotal role in the proactive design and evaluation of manufacturing environments, with a significant focus on operator health and safety. The integration of DHMs allows for the simulation and analysis of human interactions within virtual workspaces, enabling the early detection and mitigation of potential ergonomic hazards. By employing DHMs, organizations can address human factors during the design phase, leading to informed decisions about workplace and equipment design. The applications of DHMs are vast, encompassing assessments of hand clearance, reach, and spatial accommodation.